Potential of Cr(2)AIC ternary carbide as material for bipolar plate in PEMFC - Jayaraj, Jayamani; Han, Jae Ho; Park, Sang Whan; Kim, Ki Bae; Fleury, Eric (ADVANCES IN NANOMATERIALS AND PROCESSING, PTS 1 AND 2, 2007)
In this paper, we present results of an investigation on the physical, mechanical, chemical properties and processing ability of the Cr2AlC ternary carbide bulk material synthesized by hot pressing technique. The combination of excellent properties indicated that Cr(2)AIC ternary carbide alloy could be potential candidate materials as bipolar plates in polymer membrane fuel cell (PEMFC).